Hybrid Palatoplasty: A Simplified DOZ (Double Opposing Z Plasty) with Palatal Myoplasty for Primary Palate Repair - Damalachervu, Mukunda Reddy; Yellinedi, Rajesh; Nuvvula, Rambabu; A., Dharanipriya (Indian Journal of Plastic Surgery, 2023)
Introduction Surgical techniques for soft palate repair aiming for zero velopharyngeal insufficiency (VPI) are still not achieved. Straight line closure of the soft palate by various techniques of intravelar veloplasty (IVVP) leads to higher incidence of VPI due to scar contracture. Furlow's Z plasty has long, narrow, thin mucosal flaps and mucomuscular flaps with malaligned muscle closure. We present a technique of “hybrid palatoplasty” which borrows from and adds to the existing methods, is robust, is easy to replicate, and results in normal speech consistently.Aim (1) To design a technique of “hybrid palatoplasty”—combining double opposing Z (DOZ) plasty and IVVP, which is applicable to all types of cleft palate. (2) To evaluate the results of cleft palate children operated using the technique of “hybrid palatoplasty” from 2014 to 2015 in terms of surgical complications (fistulae and dehiscence) and incidence of VPI.Methods Our procedure combines aspects of both DOZ and IVVP. It is simplified with design of smaller Z plasties. On one side, from the oral Z plasty muscle is dissected off and sutured to the nasal mucomuscular flap of the opposite side to complete the palatal sling. Oral Z plasty is purely mucosal and reverse of the nasal side. A total of 123 cases, operated below 5 years of age were followed up. Speech was assessed by direct evaluation and tele-evaluation.Results A total of 123 cases, below 5 years of age, were operated between 2014 and 2016 with at least 5 years of follow-up. Note that 120 had normal speech, and 3 had VPI of which 2 were subsequently corrected and went on to develop normal speech.Conclusion This novel “hybrid palatoplasty” is a simple technique with good speech outcome as it combines the principles of Z plasty and direct muscle repair with palatal sling formation.
Keywords: palatoplasty; Furlow's Z plasty; intravelar veloplasty